2007
DOI: 10.1016/j.tet.2007.03.120
|View full text |Cite
|
Sign up to set email alerts
|

Exploring molecular recognition pathways within a family of gelators with different hydrogen bonding motifs

Abstract: General rights Copyright for the publications made accessible via the Queen's University Belfast Research Portal is retained by the author(s) and / or other copyright owners and it is a condition of accessing these publications that users recognise and abide by the legal requirements associated with these rights. AbstractWe report the synthesis of a family of gelators in which alkyl chains are connected to the amino groups of L-lysine methyl ester using a range of different hydrogen bonding linking groups (ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 61 publications
0
38
0
Order By: Relevance
“…The smaller fibres associated with C6R will constitute a network with a larger number of contact points and greater degree of entanglement, supportive of the higher T gel value. 18 Crucially, the different morphologies, must result from differing amine chirality leading to diastereomeric complexes with differing assembly modes.…”
Section: Gelation With Different Enantiomersmentioning
confidence: 99%
“…The smaller fibres associated with C6R will constitute a network with a larger number of contact points and greater degree of entanglement, supportive of the higher T gel value. 18 Crucially, the different morphologies, must result from differing amine chirality leading to diastereomeric complexes with differing assembly modes.…”
Section: Gelation With Different Enantiomersmentioning
confidence: 99%
“…In contrast, gels with 1 , 2 , or 3 as gelators, having been stored for 2 months in sealed bottles, at room temperature, resulted in phase separation. This is not a surprising result considering that 1, 2, or 3 must have reacted with the base (the solvent), and resulted in the formation of new gelators [47][48][49], being dicholesterol-based gelators, in which two cholesteryl moieties are connected by the organic diamines (cf. Scheme 2).…”
Section: Gelation Behaviors Of the Compoundsmentioning
confidence: 99%
“…We designed a polymerizable L-lysine-based gelator 1 (Figure 1) in order to obtain thermally stable LC gels through covalently cross-linking after the formation of the fibrous networks. Two acrylate groups are introduced into the extremity of the alkyl chains of L-lysine-based bisurea gelator 3 [19][20] (Figure 1). Photopolymerization of selfassembled fibers is an effective method to produce stable gels.…”
Section: Resultsmentioning
confidence: 99%
“…We focused on the lysine scaffold to design hydrogen-bonded gelators. [17][18][19][20] In our previous study, it was found that the lysinebased gelators can be used for light-scattering electrooptical materials exhibiting high contrast, low driving voltage and fast response times. 6 Therefore, the introduction of polymerizable groups into the lysinebased gelators is expected to produce efficient and stable lightscattering nematic LC gels.…”
Section: Introductionmentioning
confidence: 99%